ITE Law, Social Media, Melenial ITE ACT ON THE EFFECT OF SOCIAL MEDIA ON THE GENERATION OF MILENIAL - Andre Pebrian (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
Abstract : Social media is a telecommunication tool that is currently developing very fast, the development of social media certainly has a very significant influence, especially in daily activities, social media which is currently considered a primary need causes a lot of content that makes social media a community reference to find or provide information related to things that are happening or content that is currently trending. However, in the realization on social media, many users do not know and understand the legal basis set by the government, so that users are unaware of the consequences related to excessive use of social media, such as posting negative things and information containing SARA. The purpose of this study was to determine the ITE Law on the Effects of Social Media on Melenial Generations. The method used is descriptive method. Data collection techniques are interview and questionnaire techniques, while the data analysis techniques are qualitative. The results of this study indicate that the ITE Law on the Effects of Social Media on the Melenial Generation, namely, the ITE Law as a barometer of the activity of the millennial generation on the influence of social media, the ITE Law limits the activities of the melennial generation in expression on social media, the ITE Law is a fortress to filter out bad influences that enter through social media towards the development of the melenial generation and the form of technological developments that have spread throughout the world.